Muara Takus Temple in the digital dimension: increasing historical understanding through augmented reality - Bunari, Bunari; Isjoni, Isjoni; Fikri, Asyrul; Yuliska, Yuliska (Journal of Education and Learning (EduLearn), 2025)
This research aims to investigate the impact of using augmented reality (AR) at Muara Takus Temple as a source of history learning for students' historical understanding. Experimental research methods were involved in this research. 88 secondary school students were used as samples. They were split into two groups, the experimental group and the control group, each of which had 44 randomly chosen participants. A history test and a questionnaire used for collecting data. Historical understanding data was analyzed using statistical analysis such as the t-test to compare differences between the experimental group and the control group. Data from the questionnaire was analyzed descriptively to identify user experience and satisfaction with the AR application. The computed t score of 6.21 is significantly higher than the 2.00 t table value. These findings indicate that the use of AR in history learning can increase student understanding and engagement. Apart from that, the use of AR also increases students' interest, motivation and interaction abilities and provides immersive experiences in history learning. This research confirms that AR has great potential to improve students' historical understanding while stimulating their interest, motivation, and interaction abilities in history subjects.